Business Civilization in Decline - Heilbroner Robert L (W.W. Norton & Company, 1976)
Acknowledgements, Preface, The Immediate Future, The Middle Distance, ''Postindustrial'' Capitalism, Capitalism and the Multinational Corporation, The Long Run, Index.